Development of Sustainable Catalytic Pathways for Furan Derivatives - Liu, Xiaofang; Yu, Dayong; Yang, Wenjia; Zhang, Qiuyun; Wu, Hongguo; Li, Can (Frontiers in Chemistry, 2021)
Biomass, the only globally available, renewable feedstock of organic carbon, is considered a viable alternative to fossil fuels. It can be efficiently utilized to produce various building blocks in accordance with green and sustainable chemistry principles. In this review, recent progress, such as the transformation of carbohydrates (C5 or C6 sugar, inulin, and cellulose) and their derivatives (furfural, hydroxymethylfurfural) into significant platform chemicals over polyoxometalates, zeolites, non-noble metals, and ionic liquids in single or multiphase, is evaluated.